Framework for Research Gaps in Pediatric Ventilator Liberation - Abu-Sultaneh, Samer; Iyer, Narayan Prabhu; Fernández, Analía; Tume, Lyvonne N.; Kneyber, Martin C.J.; López-Fernández, Yolanda M.; Emeriaud, Guillaume; Ramnarayan, Padmanabhan; Khemani, Robinder G.; Baranwal, Arun Kumar; Blackwood, Bronagh; Craven, Hannah J.; et al. (Elsevier, 2024)
Background: The 2023 International Pediatric Ventilator Liberation Clinical Practice Guidelines provided evidence-based recommendations to guide pediatric critical care providers on how to perform daily aspects of ventilator liberation. However, because of the lack of high-quality pediatric studies, most recommendations were conditional based on very low to low certainty of evidence. Research Question: What are the research gaps related to pediatric ventilator liberation that can be studied to strengthen the evidence for future updates of the guidelines? Study Design and Methods: We conducted systematic reviews of the literature in eight predefined Population, Intervention, Comparator, Outcome (PICO) areas related to pediatric ventilator liberation to generate recommendations. Subgroups responsible for each PICO question subsequently identified major research gaps by synthesizing the literature. These gaps were presented at an international symposium at the Pediatric Acute Lung Injury and Sepsis Investigators meeting in spring 2022 for open discussion. Feedback was incorporated, and final evaluation of research gaps are summarized herein. Although randomized controlled trials (RCTs) represent the highest level of evidence, the panel sought to highlight areas where alternative study designs also may be appropriate, given challenges with conducting large multicenter RCTs in children. Results: Significant research gaps were identified in six broad areas related to pediatric ventilator liberation. Several of these areas necessitate multicenter RCTs to provide definitive results, whereas other gaps can be addressed with multicenter observational studies or quality improvement initiatives. Furthermore, a need for some physiologic studies in several areas remains, particularly regarding newer diagnostic methods to improve identification of patients at high risk of extubation failure. Interpretation: Although pediatric ventilator liberation guidelines have been created, the certainty of evidence remains low and multiple research gaps exist that should be bridged through high-quality RCTs, multicenter observational studies, and quality improvement initiatives.
Keywords: airway extubation; clinical protocols; mechanical ventilators; pediatric ICUs; ventilator weaning